Do you know this syndrome? Type 2 benign symmetric lipomatosis (launois-bensaude) - Esposito, Ana Cláudia Cavalcante [UNESP]; Munhoz, Tania [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP]; Miot, Hélio Amante [UNESP] (FapUNIFESP (SciELO), 2016)
A 57-year-old female showed bulky, loose tumors, which progressively spread to her arms, anterior chest, and back. She reported dysphagia and dyspnea after mild exertion. She denied alcohol consumption. CT scan of her chest showed no internal lesions. Benign symmetric lipomatosis is a rare syndrome, clinically described as multiple nonencapsulated lipomas of various sizes and symmetrical distribution. This syndrome has three known phenotypes; in type 2 (Launois-Bensaude syndrome), lesions occur primarily on the shoulders, upper arms, and chest, and is unrelated to alcoholism. It causes aesthetic deformities and might block the upper airways. Mediastinal invasion might occur as well.
Keywords: Lipoma; Lipomatosis; Multiple symmetric lipomatosis